6-Gingerol alleviates placental injury in preeclampsia by inhibiting oxidative stress via BNIP3/LC3 signaling-mediated trophoblast mitophagy - Li, Anna; Zhao, Man; Yang, Zexin; Fang, Zhenya; Qi, Weiyi; Zhang, Changqing; Zhou, Meijuan; Guo, Junjun; Li, Shuxian; Wang, Xietong; Zhang, Meihua (Frontiers in Pharmacology, 2023)
Preeclampsia (PE) is the leading cause of maternal and fetal morbidity and mortality worldwide. Apoptosis of trophoblast cells induced by oxidative stress is a principal reason of placental injury in PE. 6-Gingerol, an antioxidant from ginger, plays an important role in many disease models, but its effect on obstetric diseases has not been elucidated. In this study, we investigated the protective effect of 6-gingerol against placental injury. For this purpose, both in vitro hypoxia/reoxygenation (H/R) model of HTR8/Svneo cells and preeclamptic mice model were established to simulate PE. We found that H/R treatment induced cell apoptosis, increased the production of reactive oxygen species, malondialdehyde and lactate dehydrogenase, and decreased superoxide dismutase in trophoblast. In addition, the polarization of mitochondrial membrane potential and the cellular calcium flux were also destroyed under H/R condition, which also activated BCL2-interacting protein 3 (BNIP3) and provoked excessive mitophagy. Importantly, 6-Gingerol reversed these corrosive effects. Furthermore, the placenta damage in PE-like mouse caused by the cell apoptosis, oxidative stress injury and mitophagy of placenta in PE-like mice werewas mitigated by 6-Gingerol. These findings suggest that 6-Gingerol exerts a protective effect against placental injury in PE by reducing oxidative stress and inhibiting excessive mitophagy caused by mitochondrial dysfunction.